Media Uno Card dalam Peningkatan Kosakata Bahasa Jerman - Hijrah Fatimah; Abdul Kasim Achmad; Syarifah Fatimah (Universitas Negeri Makassar, 2024)
Abstract. This study aims to the determine the planning, implementation, and the result of the German vocabulary mastery through the uno card of class XII MIPA 6 students of SMAN 3 Makassar. This research is a classroom action study consisting of two cycles each of which contains the planning, implementation, observation, and reflection. The data of this study contains two types of data, qualitative data that is a description of the implementation results and observation results while quantitative data in the form of German language vocabulary test results. The results of research data show that the mastery of German vocabulary in cycle 1 has an average value of 55.25 and in cycle 2 has an average of 82.25. It shows an increase in the mastery of the German vocabulary of students by using the Uno Card MediaKeywords: Learning Media, Vocabulary mastery, Germany, Uno Card